Pengembangan Media Pembelajaran Pakapin Pada Pembelajaran Tematik Siswa Kelas III Sekolah Dasar Negeri Wadukopa - Feni Febrianti; Nurhasanah Nurhasanah; Itsna Oktaviyanti (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
This study aims to determine the practicality of the smart pocket board (PAKAPIN) media for third grade students at SDN Wadukopa. The results of this study are expected to be useful theoretically and practically. This research method uses 4-D (ie define, design, develop, and disseminate). The subjects of this study were 10 students of class III SDN Wadukopa in the 2021 academic year. The data collection instruments in this study used media validation sheets, material validation and student response questionnaires to the media. Data analysis was carried out by qualitative analysis and quantitative analysis. Based on the research results, the material validators get an average score of 92.7, the media validators get an average score of 80%, the media response validators get a score of 94%, the response validators of 10 students get an average score of 74.62%. Therefore, the media (PAKAPIN) is considered